Contributos da realidade virtual na reabilitação motora de idosos - Pinto, Vanda Maria Pereira; Fernandes, Sílvia da Costa; Seara, Maria de Lurdes Pereira dos Santos (Revista Recien - Revista Científica de Enfermagem, 2024)
Conhecer os contributos da realidade virtual na reabilitação motora de idosos. Estudo realizado segundo o protocolo scoping Review, e os princípios preconizados pelo Joanna Briggs Institute e Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. Os critérios de inclusão foram definidos pela mnemónica “PCC” (população, conceito, contexto). Foram incluídos artigos em inglês, espanhol e português, publicados nos 5 anos anteriores ao presente estudo. A realidade virtual, pode ser usada como ferramenta de reabilitação ortopédica para a recuperação funcional motora. Produz aumentos no volume de substância cinzenta nas regiões motora e pré-motora do hemisfério afetado após acidente vascular cerebral. Melhora o processo cognitivo neuronal de antecipação motora e reduz a ativação compensatória do hemisfério contralateral. A realidade virtual é útil e eficaz, principalmente, para os clientes com sequelas de acidente vascular cerebral, doença de Parkinson, e do foro ortopédico. Descritores: Realidade Virtual, Reabilitação, Destreza Motora, Idoso. Contributions of virtual reality in the motor rehabilitation of elderly people Abstract: To find out what virtual reality can contribute to motor rehabilitation in the elderly. This study was carried out according to the scoping review protocol and the principles recommended by the Joanna Briggs Institute and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. The inclusion criteria were defined by the mnemonic “PCC” (population, concept, context). Articles in English, Spanish and Portuguese published in the 5 years prior to the present study were included. Virtual reality, can be used as an orthopedic rehabilitation tool for motor functional recovery. It produces increases in gray matter volume in the motor and premotor regions of the affected hemisphere after stroke. It improves the neuronal cognitive process of motor anticipation and reduces compensatory activation of the contralateral hemisphere. Virtual reality is useful and effective, especially for clients with stroke sequelae, Parkinson's disease and orthopedic conditions. Descriptors: Virtual Reality, Rehabilitation, Motor Dexterity, Elderly. Aportes de la realidad virtual en la rehabilitación motora de las personas mayores Resumen: Averiguar qué puede aportar la realidad virtual a la rehabilitación motora en ancianos. Este estudio se llevó a cabo según el protocolo de revisión exploratoria y los principios recomendados por el Instituto Joanna Briggs y la Extensión para revisiones exploratorias de Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Los criterios de inclusión se definieron mediante la nemotecnia «PCC» (population, concept, context). Se incluyeron artículos en inglés, español y portugués publicados en los 5 años anteriores al presente estudio. La realidad virtual, puede ser utilizada como herramienta de rehabilitación ortopédica para la recuperación funcional motora. Produce aumentos del volumen de materia gris en las regiones motoras y premotoras del hemisferio afectado tras un ictus. Mejora el proceso cognitivo neuronal de anticipación motora y reduce la activación compensatoria del hemisferio contralateral. La realidad virtual es útil y eficaz, especialmente para clientes con secuelas de ictus, enfermedad de Parkinson y afecciones ortopédicas. Descriptores: Realidad Virtual, Rehabilitación, Destreza Motora, Ancianos.